The effect of learning opportunity factors and efficacy belief on mathematical knowledge in the teaching process (Asian Journal of Educational Technology, 2023)
The present study investigates the influence of opportunities to learn (OTL) and mathematics teaching efficacy beliefs (MTEB) towards mathematical knowledge for teaching (MKT). Using a structured questionnaire together with paper and pencil test adapted from the literature reviewed, data were collected from 187 pre-service elementary teachers in Institute of Teacher Education Indonesia. Data were analyzed using Smart PLS 3.0. The result of the structural equation model indicated that both OTL-Practicum (β = 0.395, p < 0.001) and OTL-Program (β = 0.324, p < 0.001) were positively related to MKT. The second regression analysis was to examine the impact of mathematics teaching efficacy belief on the MKT. The results showed that mathematics teaching outcome expectancy belief (MTOEB) (β = 0.322, p < 0.001) was positively related to MKT, whereas personal mathematics teaching efficacy belief (β = 0.017, p > 0.1) was not related to MKT. Overall, the belief and OTL factors explain a total of 54% variance in MKT. Implications from these findings to the successful teacher's education program implementation in Indonesia were further elaborated